A detailed study of the very high-energy Crab pulsar emission with the LST-1 - Abe, K.; Abe, S.; Abhishek, A.; Acero, F.; Aguasca-Cabot, A.; Agudo, I.; Alvarez, Crespo; Antonelli, L.; Aramo, C.; Arbet-Engels, A.; Arcaro, C.; Artero, M.; et al. (EDP Sciences, 2025)
Context. To date, three pulsars have been firmly detected by imaging atmospheric Cherenkov telescopes (IACTs). Two of them reached the TeV energy range, challenging models of very high-energy (VHE) emission in pulsars. More precise observations are needed to better characterize pulsar emission at these energies. The LST-1 is the prototype of the large-sized telescopes, which will be part of the Cherenkov Telescope Array Observatory (CTAO). Its improved performance over previous IACTs makes it well suited for studying pulsars.
Aims. In this work we study the Crab pulsar emission with the LST-1, improving upon and complementing the results from other telescopes. Crab pulsar observations can also be used to characterize the potential of the LST-1 to study other pulsars and detect new ones.
Methods. We analyzed a total of ∼103 hours of gamma-ray observations of the Crab pulsar conducted with the LST-1 in the period from September 2020 to January 2023. The observations were carried out at zenith angles of less than 50 degrees. To characterize the Crab pulsar emission over a broader energy range, a new analysis of the Fermi/LAT data, including ∼14 years of observations, was also performed.
Results. The Crab pulsar phaseogram, long-term light curve, and phase-resolved spectra are reconstructed with the LST-1 from 20 GeV to 450 GeV for the first peak and up to 700 GeV for the second peak The pulsed emission is detected with a significance level of 15.2σ. The two characteristic emission peaks of the Crab pulsar are clearly detected (> 10σ), as is the so-called bridge emission between them (5.7σ). We find that both peaks are described well by power laws, with spectral indices of ∼3.44 and ∼3.03, respectively. The joint analysis of Fermi/LAT and LST-1 data shows a good agreement between the two instruments in their overlapping energy range. The detailed results obtained from the first observations of the Crab pulsar with the LST-1 show the potential that CTAO will have to study this type of source.